Aksentuasi Nilai-Nilai Inklusif di Kalangan Pemuda Tanjung Dapura, Kota Makassar - Emanuel Omedetho Jermias; Abdul Rahman; Ashari Ismail; Jumadi Jumadi; Nurlela Nurlela (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service project aims to accentuate inclusive values among the youth of Tanjung Dapura, Makassar City, to strengthen social cohesion in a heterogeneous urban environment. The implementation methods included team consolidation, material preparation, and strategic coordination with local government authorities. The core activities were conducted through participatory counseling and Focus Group Discussions (FGD) to independently analyze social exclusion challenges. The materials focused on the importance of respecting diversity and the strategic role of youth as inclusive agents of change. The results indicated a significant increase in participants' understanding of inclusion literacy and their ability to formulate creative solutions for local discrimination issues. Evaluation through observation and reflection confirmed a paradigm shift among the youth from passive tolerance toward active participation in embracing differences. This project concludes that the synergy between critical education and collaborative dialogue successfully transforms youth into resilient pillars of social harmony. The accentuation of these inclusive values is expected to become the foundation for a more just and sustainable coastal community in Makassar.